Effect of acupuncture and massage on adolescent idiopathic scoliosis and pain severity - Jia, Kun; Yang, Yan (Frontiers in Medicine, 2025)
ObjectiveTo explore the impact of acupuncture and massage on adolescent idiopathic scoliosis (AIS) and its influence on pain degree.MethodsOne hundred and sixteen adolescent patients with idiopathic scoliosis treated from January 2021 to December 2023 were chosen to be the study objects, followed by dividing into control group and observation group. The control group received brace correction combined posture training. The observation group received traditional Chinese medicine (TCM) acupuncture and bone-setting massage treatment. The Cobb Angle, degree of pain, therapeutic effect, quality of life, incidence of adverse reactions and spinal function were compared in 2 groups.ResultsAfter therapy, the Cobb Angle value and VAS score were declined in 2 groups, and those in the observation group presented lower when comparing with the control group (P < 0.01). In contrast to the control group, the total effective rate in the observation group was better (P < 0.05), and the SRS-22 score in the observation group was higher (P < 0.05). After therapy, the ODI score was declined and JOA score was elevated in 2 groups, and the improvements of ODI and JOA scores in the observation group were more significant when comparing with the control group (P < 0.01).ConclusionAcupuncture and massage can promote the clinical treatment effect, reduce the degree of pain, promote Cobb Angle recovery, promote the quality of life and improve the spinal function of AIS.